Acute Spontaneous Rupture of the Superior Ophthalmic Vein. Issue 6 (November 2020) - Vahdani, Kaveh; Rose, Geoffrey E.
Abstract : Purpose: To describe patients presenting with sudden onset of localized hemorrhage from a presumed acute spontaneous rupture of the superior ophthalmic vein. Methods: A retrospective review of the pattern of presentation, clinical implications and outcomes, and the characteristic imaging and histologic features. Results: Six patients (5 men; 84%) presented at a mean age of 45 years (range 15–72), with the commonest symptoms and signs being acute onset of Valsalva-negative proptosis (mean 3.3 mm; range 0–7 mm), orbital pain, and diplopia; none had a known precipitating factor (such as severe Valsalva maneuver or coagulopathy). Two patients developed a mild optic neuropathy. Imaging revealed a well-defined, ovoid, homogenous soft-tissue mass above (2 cases), superomedially to (3 cases), or below the superior ophthalmic vein; the masses were typically echogenic on B-mode ultrasonography, and there was no detectable internal blood-flow. Resolution of signs and symptoms was noted in 5 patients over an average of 4.6 months (range 3–7 months), while 1 patient—the youngest—required excision of a persistent mass with increasing exophthalmos and early optic neuropathy. Conclusions: Well-localized hemorrhage from the mid-part of the superior ophthalmic vein is very rare and appears to occur spontaneously in the absence of a detectable venous-lymphatic anomaly. This event might imply a spontaneous "blowout" from an area of mural susceptibility in this part of the superior ophthalmic vein, thus forming a pseudoaneurysm. In most cases, the clinical signs slowly improve over several months, surgical intervention is not required, and recurrence appears very infrequent. Abstract : Six patients presented with a sudden onset of localized orbital hemorrhage in proximity to the midorbital portion of the superior ophthalmic vein, in the absence of any detectable underlying venous-lymphatic anomaly or systemic vasculitis. Histology from 1 case confirmed a pseudoaneurysm, with an encysted hemorrhage on the vein, and the authors propose that this part of the superior ophthalmic vein might be susceptible to acute spontaneous rupture.